Penyaring Air dengan Biolarvasida Nabati Ekstrak Rimpang Lengkuas sebagai Upaya Pengendalian Vektor Demam Berdarah - Nur Lu'lu Fitriyani; Ristiawati Ristiawati; Dewi Nugraheni Restu Mastuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Dengue Hemorrhagic Fever is a serious problem in Central Java with an Incidence Rate (IR) of 10.2/100,000 population in 2018. Efforts to reduce the number of dengue fever cannot be separated from efforts to control the Aedes aegypti vector. Alternative vector control that is safer and more environmentally friendly can be done by utilizing compounds derived from plants that have biologically active properties. The plant that has the potential to be developed as a natural insecticide is galangal (Alpinia galanga). The amis of this study was to determine the effectiveness of a water filter added with biolarvicides from galangal rhizome extract. The research method used was a quasi-experimental method with 4 different concentrations of galangal extract (0.1%; 0.2%; 0.3% and 0.4%) and used a negative control without the addition of galangal extract. The results showed that in water filter treatment with galangal rhizome extract, there was death in Ae. aegypti mosquito larvae, while in negative control there was no larval death. The results showed that mortality of Ae. aegypti mostly occurred at a concentration of 0.4% as many as 25 larvae. Water filter with galangal rhizome extract biolarvicide has the potential to kill Ae. aegypti larvae.